2012
DOI: 10.1590/s0037-86822012000600021
|View full text |Cite
|
Sign up to set email alerts
|

Severity of atopic dermatitis and Ascaris lumbricoides infection: an evaluation of CCR4+ and CXCR3+ helper T cell frequency

Abstract: Introduction: Ascaris lumbricoides-infected patients present lower prevalence of severe atopic dermatitis. Methods: Peripheral blood of infected children with atopic dermatitis was assessed by flow cytometry of the frequency of Th1 and Th2 cells through the expression of CXCR3 and CCR4 chemokine receptors, respectively. Results: Helminth-free patients with atopic dermatitis presented a high frequency of CCR4+Th2 cells. Parasitized patients with atopic dermatitis showed a lower frequency of CXCR3+Th1 cells comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Helminth infection may modulate immune responses by inducing an anti-helminthic T H 2 cytokine-dominated milieu, which may result in an allergic phenotype once the infection is removed. 88,89 Evidence in support of this comes for instance from a large placebo-controlled trial in a helminth-endemic region of Uganda, whereby treatment with albendazole during the third trimester of pregnancy was associated with an increased prevalence of AD in offspring up to 1 year. 48,90 In contrast, a randomized placebo-controlled trial of helminth eradication in a helminth-endemic area in Vietnam found no effect on the prevalence of AD in schoolchildren, when anti-helminthic treatment was administered to schoolchildren, highlighting that there may be a critical time window for immuno-modulation at the gut interface during the perinatal period.…”
Section: Gut Microbiome and Dietary Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Helminth infection may modulate immune responses by inducing an anti-helminthic T H 2 cytokine-dominated milieu, which may result in an allergic phenotype once the infection is removed. 88,89 Evidence in support of this comes for instance from a large placebo-controlled trial in a helminth-endemic region of Uganda, whereby treatment with albendazole during the third trimester of pregnancy was associated with an increased prevalence of AD in offspring up to 1 year. 48,90 In contrast, a randomized placebo-controlled trial of helminth eradication in a helminth-endemic area in Vietnam found no effect on the prevalence of AD in schoolchildren, when anti-helminthic treatment was administered to schoolchildren, highlighting that there may be a critical time window for immuno-modulation at the gut interface during the perinatal period.…”
Section: Gut Microbiome and Dietary Influencesmentioning
confidence: 99%
“…The role of the microbiome is expanded further when helminth parasites and their relationship to AD development are considered. Helminth infection may modulate immune responses by inducing an anti‐helminthic T H 2 cytokine–dominated milieu, which may result in an allergic phenotype once the infection is removed 88,89. Evidence in support of this comes for instance from a large placebo‐controlled trial in a helminth‐endemic region of Uganda, whereby treatment with albendazole during the third trimester of pregnancy was associated with an increased prevalence of AD in offspring up to 1 year 48,90.…”
Section: The Role Of the Microbiomementioning
confidence: 99%
“…Very importantly, growing evidence indicates that these helminthiases increase susceptibility to other life-threatening infections such as malaria, tuberculosis, and HIV/AIDS [5-7]. In turn, some human studies have shown that intestinal helminths can modulate the occurrence of allergies and asthma [8], alter the course of some autoimmune diseases such as multiple sclerosis [9] and inflammatory bowel disease [10], among others. The latter studies lend renewed support the “hygiene hypothesis” [11,12], more recently called the “Old Friends Hypothesis” [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of cases is small and this is not a main objective of this work, our data suggest that contrary to Ascaris tropomyosin, Asc l 5 does not have a significant impact on asthma evolution. However, more studies should be undertaken to address this point, not only in asthma [20] but also to explore the effect of Asc l 5 sensitization on other allergic diseases such as atopic dermatitis, an aspect of ascariasis that have been little investigated [38]. The strength of the IgE response to rAsc l 5 is similar to that observed in other studies against Ascaris tropomyosin or ABA-1 [9,20,39], and greater than that detected for glutathione transferase allergen (Asc l 13) [8,20].…”
Section: Discussionmentioning
confidence: 99%